Il teatro delle piccole cose: Quiet Ensemble (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
This essay explores the work of Quiet Ensemble, a cross-media factory by artist-performers Fabio Di Salvo and Bernardo Vercelli. My analysis begins from the concept of Liveness (Auslander, 1999) as it relates to recent reflections on art and media practices in on and off-line environments and is intended to contribute to a mapping of new Italian performance practices. In my opinion Quiet Ensemble’s performances opens various degrees of complexity that further expand the concept of Liveness. Di Salvo and Vercelli have created live performances since 2009. Their work is located at the intersection of art, video, theater and digital music. They present highly technological shows and installations created with “elements” from the natural world - such as sunlight, mice, bees, fish and more. The performances are created by the random interaction of these “elements” with the digital framework controlled live, on stage, by Di Salvo and Vercelli.
Keywords: liveness, nature, organic, offline performance, crossmedia.